Tinjauan Terhadap Pelayanan Yang Relevan Oleh Unlimited Fire Youth Conference - Lewisinki Naftaliance; Fibry Jati Nugroho; Iskak Sugiyarto (Institut Agama Kristen negeri Kupang, 2021)
The wave of the technological revolution has a strong correlation with the globalization process which has succeeded in creating a new culture and lifestyle in society. With or without realizing it, the world is undergoing a transition process, which is quite a change. These changes can bring about both change and disaster in particular for young people. From the available data, it can be seen that the decreasing interest of young people to worship. Relevant services are needed in responding to technological developments in the era of the industrial revolution. The discussion in this article emphasizes how to serve young people in today's context and according to their style and language but still based on the truth of God's Word. In writing this article using a descriptive analysis method with a qualitative approach. The Unlimited Fire Youth Conference is an example of a relevant youth conference and community. By maximizing the use of existing social media to reach and serve young people.